Revenue Analysis Of Intecropping Farming Between Corn And Sweet Potato - Hamidah, Emmy; Santi, Idum Satia; Abdullah, Rizqi Putu (Akademi Komunitas Perkebunan Yogyakarta, 2025)
The study of income analysis of intercropping between corn and Sweet potato in Kediren Village, Kalitengah District, Lamongan Regency aims to determine the income of sweet potato farming and sweet corn farming. This research was conducted from September to November 2024 The method used in this study was a survey. Data collection was carried out through interviews and observations. Sampling used a non-probability sampling technique. The population in this study amounted to 30 people so that all respondents were taken as samples. The location of the study in Kediren Village, Kalitengah District, Lamongan Regency was determined purposively because it met the criteria set by the researcher. Thus, it is expected to answer the existing problems. Based on the research results, it can be seen that the production costs of farmers who carry out corn and sweet potato intercropping in Kediren Village, Kediren District, Lamongan Regency, it can be seen that the total cost of corn and sweet potato intercropping is Rp. 32,337,400,–. Corn income is 18,618,400,– and sweet potato is Rp. 13,719,000,–. The difference in income between corn and sweet potatoes is Rp 4,899,400,-. This study shows that the harvest that is only planted with corn, the income is Rp 32,000,000,- compared to intercropping between corn and sweet potatoes, the income is Rp 54,200,000,-